An evaluation of the effectiveness of employee wellness management programme in the Department of Agriculture in Capricorn District of Limpopo Province - Makgato, Mollale Dorcus (University of Limpopo, 2016)
Wellness Management strives to meet the health and wellness needs of the public servants through diverse preventative and curative measures by customizing those aspects from traditional programmes such as Employee Assistance Programme (EAP), Work life Balance and, Wellness Management programmes. These are the most relevant and fit the uniqueness of the public service and its mandate. The provision of such diverse programmes is vital in the public service setting. In order to determine the effectiveness of these programmes, an evaluation is therefore necessary to validate its existence in fulfilling its objectives and furthermore, improving its performance. The aim of this research study was to evaluate the effectiveness of Wellness Management Programme (WMP) in the Department of Agriculture in the Capricorn District, concentrating on the provision, utilization and awareness of the programme. The study also investigate the benefits of the programme to both the employee and the employer and the extent to which they derive value in the programme. Supervisors and supervisees respectively were interviewed, and they both regarded the programme as effective and furthermore as a good and suitable option in improving job performance in the department. However, the utilization of the programme is mainly from employees in the administration field, with less utilization from technical employees, which further calls for promotion of the programme to technical/core employees and their management. The majority of respondents were aware of the programme and are currently satisfied with the accessibility of coordinators of the programme, although the challenge is still with EAP services. The centralisation of EAP at Provincial office delays progress and effective utilization of the services and therefore decentralisation of the services to district office, the recruitment of qualified professionals and establishment of EAP Advisory Committees are recommended. The majority of supervisors and supervisees who had utilised the services have seen improvements in their lives and their job performance, hence they still recommend the services to other colleagues. Management support and involvement through the provision of advises, budget and so forth is crucial in the improvement of the programme utilization.
Thesis (M. Dev.) -- University of Limpopo, 2016
Keywords: Employee wellness management programme; Employee health education